1999
DOI: 10.1177/096368979900800304
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytochrome P450 IA1 Activity of Self-Assembled Rat Hepatocyte Spheroids

Abstract: Primary rat hepatocytes can self-assemble to form multicellular spheroids when plated onto Primaria petri dishes. Spheroids have been observed to exhibit enhanced liver-specific functions and differentiated ultrastructure compared to monolayer cultures on dry collagen. With confocal scanning laser microscopy, CYP1A1 activity was evaluated in situ by detecting resorufin. This highly fluorescent molecule is the P450-mediated product of 7-ethoxyresorufin O-dealkylation (EROD). Significantly higher P450 activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…The sustained functions are synchronous to structural and morphological characteristics of spheroids, including the existence of tight cell-cell contact, retention of cell-cell junctions, and polarization. 17,[20][21][22]46,47 Under TEM, cells in the differentiated aggregates appeared to be abundant in tight junctions at cell-cell boundaries. Bile-canaliculi-like openings possessing microvilli and delimited by tight junctions were also highly visible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustained functions are synchronous to structural and morphological characteristics of spheroids, including the existence of tight cell-cell contact, retention of cell-cell junctions, and polarization. 17,[20][21][22]46,47 Under TEM, cells in the differentiated aggregates appeared to be abundant in tight junctions at cell-cell boundaries. Bile-canaliculi-like openings possessing microvilli and delimited by tight junctions were also highly visible.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] A number of factors such as the microenvironment, cell-cell interactions, and cellular polarization may play a positive role in sustaining liverspecific functions in those hepatocyte spheroids. Thus, it is worth exploring whether such positive effects of 3D cultivation translate to the differentiation of stem cells to hepatocyte-like cells.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Analysis of the hepatic synthetic function (albumin, urea) and of hepatic metabolism (cytochrome P450 activity) showed that these three methods can maintain a high level of liverspecific function for over 4 weeks in vitro. However, analysis of LDL uptake in cultured hepatocytes was limited to nonpolarized cell lines such as HepG2, possibly due to loss of LDL-R expression in primary cultured hepatocytes.…”
mentioning
confidence: 99%
“…33 The mechanism for the increased P450 expression in spheroids is unknown, however, it is of interest that the hepatocytes in the core of the spheroid exhibit higher P450 activity than those at the surface. 34 Further support for the cell density-dependent expression of P450 2B6 reported here is provided by the observation that another human P450, P450 3A4, also undergoes cell density-dependent expression, in that case in human primary hepatocytes, where the constitutive and the inducible levels of P450 3A4 are both decreased at lower cell densities in a cell-cell contactdependent process.…”
Section: Discussionmentioning
confidence: 99%